MODEL KOMUNIKASI BISNIS DALAM BERWIRAUSAHA KULINER PASCA PANDEMI COVID-19 PADA UMKM KOTA DEPOK - Hiswanti, Hiswanti; Bachtiar, Alfan; wukir, Iswahyu Prana; Misnan, Misnan; Suandi, Fikri (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
The theory of the social construction of reality and the theory of the social construction of mass media are still partially discussed. Several previous pieces of research have not yet correlated, elaborated, or synthesized from the theoretical aspect. Even though much has been said about the social construction of reality, media consumers are heavily influenced by media "made" constructions. The research aims to synthesize the Bergerian theory of social reality construction (Berger and Luckmann) with the Bunginan theory of social reality construction (Burhan Bungin). The method used is a literature study. The results showed that the synthesis of the social construction theory of reality and the social construction of mass media reality produced a thesis understanding of an objective and subjective reality which was sufficiently understood through the social construction theory of mass media reality. This is considering the individual phenomenon which, in all durations of daily life, cannot be separated from the role of social media interaction. They externalize, objectify as well as internalize reality based on mass media references. In the hierarchy, the social construction theory of reality can be placed as a grand theory by considering genealogical aspects, while the social construction theory of mass media reality can be placed as a middle-rank theory. This is of course related to the more universal focus on social construction of reality.This research aims to analyze an effective business communication model in the context of culinary entrepreneurship post the COVID-19 pandemic, particularly in Micro, Small, and Medium Enterprises (MSMEs) in Depok City. The COVID-19 pandemic has significantly impacted the culinary sector, with social restrictions and changes in consumer behavior. Therefore, it is crucial to understand how culinary MSMEs can adapt and succeed in facing these challenges.This study employs a qualitative approach, utilizing in-depth interviews with culinary MSME owners in Depok City. The data collected are analyzed using thematic analysis to identify emerging patterns and findings. The research findings indicate that an effective business communication model for culinary MSMEs post the COVID-19 pandemic involves several key elements. Firstly, MSMEs need to have a clear and targeted communication strategy, including identifying the appropriate target market and developing relevant messages. Secondly, the utilization of digital and online media is crucial in promoting products and reaching potential consumers. MSMEs need to leverage social media, websites, and online booking platforms to enhance product visibility and accessibility. Furthermore, collaboration with relevant stakeholders is also an essential factor in a successful business communication model. MSMEs can establish partnerships with local suppliers, culinary communities, and government institutions to expand their reach and gain necessary support.This research provides valuable insights for culinary MSMEs in Depok City and similar sectors in developing effective business communication models post the COVID-19 pandemic. By adopting these approaches, MSMEs can enhance their chances of success in facing challenges and capitalizing on emerging opportunities amidst changing consumer behavior and intensifying competition in the post-pandemic era.